The Eucalyptus linker histone variant EgH1.3 cooperates with the transcription factor EgMYB1 to control lignin biosynthesis during wood formation - Soler, Marçal (The New phytologist, 2017)
© 2016 The Authors. New Phytologist © 2016 New Phytologist Trust.